Participación de las mujeres indígenas en la comunidad Zenú del Distrito de Barrancabermeja - López Rocha, Nadith (Universidad Antonio Nariño, 2024)
The research focused on analyzing the political participation of indigenous women belonging to the Zenú council in the district of Barrancabermeja, Santander, through a descriptive methodology of mixed approach. The results obtained showed that the participation of Zenú women, like other vulnerable social groups, is limited by various factors, especially violence, racial discrimination, cultural barriers and gender inequality